Adverse event reporting patterns of concomitant botanical dietary supplements with CYP3A4 interactive & CYP3A4 non-interactive anticancer drugs in the U.S. Food and Drug Administration Adverse Event Reporting System (FAERS). Issue 2 (1st February 2019) - Fahim, Shahariar Mohammed; Mishuk, Ahmed Ullah; Cheng, Ning; Hansen, Richard; Calderón, Angela I.; Qian, Jingjing
ABSTRACT: Background : To examine the adverse event (AE) reporting patterns for concomitant Botanical Dietary Supplements (BDS) and anticancer drugs. Research design and methods : Using the 2004–2015 U.S. Food and Drug Administration Adverse Event Reporting System (FAERS) database, AEs involving commonly used BDS and anticancer drugs (categorized into CYP3A4 interactive and CYP3A4 non-interactive) were examined. Disproportionality analyses using reporting odds ratios (RORs) assessed the relative reporting rates of 1) serious AEs (i.e., mortality and morbidity) with concomitant use of BDS (overall and by type) and anticancer drugs compared to anticancer drugs only; and 2) AEs by specific System Organ Classes (SOCs). Results : A total of 3, 264 AEs were reported involving concomitant BDS and CYP3A4 interactives, and 3, 885 involving concomitant BDS and non-interactive anticancer drugs. ROR of serious AEs with concomitant all BDS and anticancer drugs compared to anticancer drugs alone showed a potential protective signal (ROR = 0.65, 95% CI = 0.62, 0.68), but ROR for açaí and non-interactive anticancer drugs indicated potential risk (ROR = 1.70, 95% CI = 1.01, 2.86). Heterogeneity of reporting patterns of AEs related to certain SOCs was observed for use of BDS along with anticancer drugs. Conclusion : This study identified potential protective and risk signals for AEs with concomitant use of BDS and anticancer drugs.